"Was wäre, wenn ich die Sonne wäre?” Ein Beispiel aus der schulpraxisorientierten Erforschung induktiver Lehrverfahren im (integrierten) Grammatikunterricht - HOSTYŃSKI, Paweł (Wydawnictwo Naukowe UAM, 1997)
The article presents an exemplary fragment of empirical research based upon explorative-interpretative methodology. The research deals with forms of inductive approach to grammar teaching applied today. The presented two lessons, devoted to the introduction of conditional sentences (Konjunktiv II) chosen from a wider empirical base, have been further analyzied and discussed in the latter part of the article. The above-mentioned analysis has been completed by interviews with students who - in the majority - approve of the use of induction. The inductive approach may be one of adequate techniques of applicable within the concept of „integrierter Grammatikunterricht” (i.e. „integrated grammar teaching”), in which pressure is put on contens, situational context, developing linguistic skills, and - most of all - on the activi-sation of students and their independent, creative thinking.